UMP researcher produces milk coagulant using a mixture of extract of three local fruits - Nur Hartini, Mohd Hatta (2020)
Kuantan, 8 September 2020 - Milk coagulation is the first process for the production of cheese or curd and is usually done using enzyme extracts from the stomach of unweaned young animals such as calves, kids and piglets.